The quasi-parallel lives of satellite cells and atrophying muscle - Biressi, Stefano; Gopinath, Suchitra D. (Frontiers in Aging Neuroscience, 2015)
Skeletal muscle atrophy or wasting accompanies various chronic illnesses and the aging process, thereby reducing muscle function. One of the most important components contributing to effective muscle repair in postnatal organisms, the satellite cells, have recently become the focus of several studies examining factors participating in the atrophic process. We critically examine here the experimental evidence linking satellite cell function with muscle loss in connection with various diseases as well as aging, and in the subsequent recovery process. Several recent reports have investigated the changes in satellite cells in terms of their differentiation and proliferative capacity in response to various atrophic stimuli. In this regard, we review the molecular changes within satellite cells that contribute to their dysfunctional status in atrophy, with the intention of shedding light on novel potential pharmacological targets to counteract the loss of muscle mass.